Expression Analysis of Serotonin Receptors, Serotonin Transporter and l-Amino Acid Decarboxylase in the Mouse Sphenopalatine Ganglion by RT-PCR, Northern Blot Analysis and In Situ Hybridization. (15th July 2019) - Ishida, Yusuke; Sugiura, Yusuke; Magome, Takuya; Kamakura, Takefumi; Takimoto, Yasumitsu; Hanada, Yukiko; Kitayama, Kazuki; Nakamura, Yukiko; Shimada, Shoichi; Ohta, Nobuo; Naono-Nakayama, Rumi; Kamijo, Keiju
Abstract: The sphenopalatine ganglion (SPG) is a gathering of the cell bodies of parasympathetic fibers that dominate the nasal gland, lacrimal gland and cerebral blood vessels. The SPG controls nasal secretions, tears, and the dilation of cerebral blood vessels. However, it is unclear how serotonin regulates SPG functions. In this study, we investigated the expression of genes involved in the serotonergic system in the mouse SPG. We examined the mRNA expression levels of 5-HT1A, 5-HT1B, 5-HT1D, 5-HT1F, 5-HT2A, 5-HT2B, 5-HT2C, 5-HT3A, 5-HT3B, 5-HT4, 5-HT5A, 5-HT5B, 5-HT6 and 5-HT7 receptors, as well as serotonin transporter, tryptophan hydroxylases 1 and 2, and L-amino acid decarboxylase (AADC) by RT-PCR. It revealed that the 5-HT3A and 5-HT3B ionotropic receptors and AADC were likely to be highly expressed in the SPG, as measured by RT-PCR. We next performed in situ hybridization on the SPG to examine the expression of these three genes at the cellular level after validating the specificity of each cRNA probe by northern blotting. The 5-HT3A receptor, 5-HT3B receptor, and AADC were expressed in 96.5% ± 1.0%, 29.7% ± 10.7%, and 57.4% ± 2.9% of neuronal cell bodies in the SPG, respectively, indicating that the 5-HT3A receptor was virtually expressed in all SPG neurons. Our results on the expression of these critical serotonin system genes in the parasympathetic SPG provide insight into the pathogenetics of rhinitis, conjunctivitis and headache. Furthermore, our findings suggest that targeting the 5-HT3A receptor might have therapeutic potential in the treatment of these ailments. Highlights: The SPG controls tears, nasal secretions, and dilation of cerebral blood vessels. Expression of serotonergic system-related genes in the mouse SPG was comprehensively investigated. 5-HT3A and 5-HT3B receptors, as well as AADC, were highly expressed in the mouse SPG. The 5-HT3 ion channel receptor may be involved in the production of tears, nasal secretions, and cerebrovascular dilation. Our findings may aid in elucidating the pathophysiology of conjunctivitis, rhinitis, and headache.